Patient-specific titanium-reinforced calcium-phosphate (CaP: Ti) implants for revision cranioplasty - Paul Vincent Naser; Friederike Zacharias; Henrik Giese; Sandro M. Krieg; Andreas W. Unterberg; Alexander Younsi (Brain and Spine)
Introduction: Cranioplasty is a common neurosurgical procedure, but infections can complicate it, necessitating revision surgery. Alloplastic patient-specific implants (PSI) are increasingly utilized, and different materials are available. This study evaluates the role of titanium-reinforced calcium-phosphate (CaP:Ti) implants in revision cranioplasty. Research question: Assessing the efficacy and safety of CaP:Ti PSI in patients requiring revision cranioplasty following complications with previously failed cranioplasty attempts. Material and methods: Retrospective analysis of 15 patients who underwent CaP:Ti PSI implantation for revision cranioplasty between 2016 and 2022 at a single neurosurgical department. Data on demographics, perioperative details, and outcomes were collected and assessed. Differences in distribution were assessed using Fisher's exact test, and groups were numerically compared using student's t-test. A p-value <0.05 was considered statistically significant. Results: In most patients, CP failure occurred early (38 days) following elective craniotomy for tumor and vascular procedures. The first revision cranioplasty was conducted in 12 cases using CaP:Ti PSI in 8 cases successfully requiring no further revision. Three cases implanted with other alloplastic materials required revision and received CaP:Ti PSI in the second (n = 2) or third (n = 1) CP attempt. The overall success rate for CaP:Ti PSI was 73.3% over more than two years of follow-up. success rate in revision cranioplasty. Surgical site complications, predominantly infections, were the main cause of CP failure. The average interval between implant removal and re-cranioplasty was 300 days. Prehabilitation using skin expanders and postoperative antibiotic use were strategies successfully utilized in this cohort. Discussion and conclusion: Our findings suggest that CaP:Ti PSI implants hold promise in salvaging complicated cranioplasty in most cases despite challenges such as infection and implant failure. The use of techniques like skin expanders may contribute to better outcomes. However, further research is crucial to establish optimal timing and patient selection guidelines in revision cranioplasty using CaP:Ti implants, which could significantly impact future neurosurgical practices.